Can unilateral strength training optimize change of direction mechanics and mitigate anterior cruciate ligament injury risk in female soccer players? A preliminary pre-post intervention study - Rogalski, A.; Moiroux-Sahraoui, A.; Stergiou, M.; Pieulhet, M.; Douryang, M.; Forelli, F. (Sports, 2025)
Background: Anterior cruciate ligament (ACL) injuries are a major concern in female soccer players, with change of direction (COD) movements being a key contributor to non-contact injuries. Traditional injury prevention programs have shown limited effectiveness in addressing individual biomechanical deficits. This study aimed to evaluate the effects of a 10-week unilateral strength training program on COD mechanics and ACL injury risk factors.